Short Communication - It All Lies in Her Eyes - Jawaria Akhtar, Haroon Tayyab, (Pakistan Journal of Ophthalmology, 2016)
Eye colour is one of the most notable traits in determining facial features. In this case report, we present a 19 year old girl with isolated congenital heterochromia iridis. She presented to outdoor patient department for a routine check up. On detailed examination, we did not find any ocular or systemic abnormality. Isolated heterochromia iridis is an exceedingly rare condition world wide and in our population as well. Ophthalmologist should be aware of this condition and should be able to rule out different syndromes and ocular/systemic conditions that may be associated with it. Key words: Heterochromia iridis, melanin, Fuch’s heterochromic uveitis.